Tindak Pidana Korupsi yang Melibatkan Sektor Swasta dalam Perspektif Kejahatan Lintas Negara (Studi Perbandingan Malaysia) - Riauroikha, Hilmalia Sesy; Juniati, Rita; Simanjuntak, Vincent Anderson; Sitohang, Jeremia; Efritadewi, Ayu (UNES Law Review, 2023)
Corruption is a serious problem that harms state finances, the social and economic rights of the people, and hampers development. Corruption in the private sector has also become a serious threat to the economies of countries such as Indonesia and Malaysia. This article discusses the approaches taken by Indonesia and Malaysia in addressing corruption involving the private sector.Indonesia recognizes that corruption in the private sector is a serious threat and has strengthened rules and regulations related to corporate transparency and accountability. Laws governing corruption prevention cover the private sector, and the government encourages ethical business practices. Indonesia also strengthens international cooperation and takes decisive action through independent law enforcement agencies.In Malaysia, corruption in the private sector also receives serious attention. Malaysia has strong laws against corruption, including in the private sector. The country has successfully uncovered and prosecuted corruption cases involving private companies in a transparent and decisive manner. Malaysia is also active in international cooperation and has an effective anti-corruption agency.While both countries have taken concrete steps to fight corruption in the private sector, there are still challenges to overcome, such as the involvement of powerful actors and the complexity of corruption cases. However, by strengthening rules, strict law enforcement, enhancing international cooperation, and involving the public and international institutions, Indonesia and Malaysia can continue to effectively combat corruption involving the private sector.